Prospects of bicar as soil amendment in Nepal hill farming systems - Dahal, Ngamindra; Bajracharya, Roshan Man; Merz, Juerg (Journal of Agriculture and Environment, 2018)
Burning of biomass under controlled temperature and oxygen limited environment produces biochar along with syn-gases and bio-oil. A significant volume of literatures portray biochar as a remedial option to meet growing needs of amending agricultural soils for global food security and carbon sequestration to curb climate change. Biochar has generated huge interests among agro-practitioners mainly for its two sets of benefits. The first set of benefits is about desirable changes in soil function that includes enhanced soil microbial activity, retention of nutrients and moisture, alkaline effect for treating acidic soils and, increased porosity on soil structure. The second set includes enhanced adaptive capacity of agricultural systems to climate change impacts, and, carbon sequestration due to its recalcitrant nature that remain in soil for a very long period. These acclaimed effects of biochar on soils are among the much sought-after remedies to heal a number of soil health ailments that millions of farmers and policy planners are looking for. However, effectiveness of biochar has yet to be examined carefully in different soil types over diverse topography corresponding with local cropping patterns. Matching properties of soils with those of biochar is a prerequisite for any interventions aimed at soil amendment. Properties of biochar generally depend on feedstock types, and temperatures during pyrolysis. This review analyses major published works on different aspects of biochar with the key question of whether promotion of biochar could be a viable solution to address some of the critical concerns of soil productivity in the Nepal mid hills and concludes with a note that there are serious knowledge gaps in two fronts – systematic practice of biochar production and application in agricultural farms is yet to take off, and, documented evidences of effectiveness of biochar on various soil types and cropping patterns are insignificant.